2022
DOI: 10.1097/jhq.0000000000000335
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Discharge Medication Reconciliation Across a Five-Hospital Health System

Abstract: Purpose:Hospital readmission of a primary diagnosis can have a substantial financial impact via reductions in reimbursement rates up to 3%, and have a negative impact on the lives of patients. Discharge medication reconciliation (DMR) can reduce medication errors that play a role in readmission. The objective of this study is to evaluate the impact of expanding pharmacist-led DMR across a four hospital health system on 30-day readmission rate for high risk of readmission disease groups.Methods:During the 3-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…1,2 Pharmacist-led medication reconciliation at discharge (PMRD) has emerged as a potential solution to enhance medication safety by mitigating medication errors and reducing hospital readmissions. [3][4][5][6][7] Hospital discharge is a phase of care in which patients often become more vulnerable due to the absence of monitoring and assistance with medication administration. Previous publications from the Multi-Center Medication Reconciliation Quality Improvement Study have revealed a reduction in potentially harmful discrepancies in admission and discharge orders through a multifaceted medication reconciliation implementation model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Pharmacist-led medication reconciliation at discharge (PMRD) has emerged as a potential solution to enhance medication safety by mitigating medication errors and reducing hospital readmissions. [3][4][5][6][7] Hospital discharge is a phase of care in which patients often become more vulnerable due to the absence of monitoring and assistance with medication administration. Previous publications from the Multi-Center Medication Reconciliation Quality Improvement Study have revealed a reduction in potentially harmful discrepancies in admission and discharge orders through a multifaceted medication reconciliation implementation model.…”
Section: Introductionmentioning
confidence: 99%
“…Medication discrepancies and errors occurring during hospital discharge represent a critical concern, posing significant risks such as adverse patient outcomes, medication‐related readmissions, and increased health care costs 1,2 . Pharmacist‐led medication reconciliation at discharge (PMRD) has emerged as a potential solution to enhance medication safety by mitigating medication errors and reducing hospital readmissions 3–7 …”
Section: Introductionmentioning
confidence: 99%